OPERASI KONTRA TEROR KOALISI GLOBAL DALAM MENGHADAPI PERGERAKAN ISLAMIC STATES OF IRAQ AND SYIRIA (ISIS) - Azhari Setiawan; Alfajri Alfajri (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2018)
ABSTRACT This study reveals the movement of the Islamic State of Iraq and Syria (ISIS) from two perspectives that are essentially contradictory. These two points of view are related to the relationship between the distribution of capabilities between actors in the Middle East and ISIS movements. The first point of view sees that ISIS is a consequence of the distribution of capability of actors in the Middle East, while the second point of view sees that ISIS is a determinant of the distribution of capabilities in the Middle East. There are two main arguments to see the relationship between the distribution of actor capabilities in the current international system and the emergence and development of ISIS. First, the distribution of capability of actors in the international system (Middle East) caused ISIS to be borned and developed. Second, on the contrary, the movement and development of ISIS in the Middle East influenced the distribution of capability of related actors in the international system (Middle East and surrounding areas). The first thesis emphasizes that the distribution of capabilities and conditions of the international system in the Middle East triggered/motivated the birth of ISIS. In this case ISIS becomes dependent variable. Then, the second thesis emphasizes the influence of ISIS on the conditions of the international system. It means that, it is ISIS movement that influenced the distribution of capabilities among actors in the international system. The distribution of US power that decided to enter the Middle East [starting from the participation of the United States in the Gulf War, the invasion of Iraq, the Arab Spring, etc.] triggered the birth of protest movements which led to the Asymmetric War against terrorism. The participation of other major countries in the Middle East conflict contributed to the situation in the Middle East. The distribution of power in Iraq and Syria greatly affected the birth of ISIS. Keywords: ISIS, Arab Spring, United States of America, Power Distribution ABSTRAK Penelitian menjelaskan gerakan Islamic State of Iraq and Syiria (ISIS) dari dua perspektif yang berbeda. Kedua perspektif tersebut berkaitan dengan distribusi kapabilitas antara berbagai aktor di Timur Tengah dan ISIS. Perspektif pertama melihat bahwa ISIS merupakan konsekuensi dari distribusi kapabilitas aktor di Timur Tengah, sementara perspektif kedua melihat bahwa ISIS merupakan determinan distribusi kapabilitas tersebut. Terdapat dua argumen untuk melihat hubungan antara distribusi kapabilitas aktor dalam sistem internasional kontemporer dan kemunculan sekaligus perkembangan ISIS. Pertama, distribusi kapabilitas aktor sistem internasional pada tingkat kawasan Timur Tengah menjadi penyebab kemunculan dan perkembangan ISIS. Kedua, pergerakan dan perkembangan ISIS di Timur Tengah dipengaruhi oleh oleh distribusi kapabilitas aktor-aktor terkait dalam sistem internasional di Timur Tengah dan kawasan sekitarnya. Argumen pertama menekankan bahwa distribusi kapabilitas dan kondisi sistem internasional di Timur Tengah menjadi penyebab kemunculan ISIS. Dalam hal ini ISIS menjadi variabel dependen. Argumen kedua menekankan pengaruh ISIS terhadap kondisi kapabilitas antar aktor dalam sistem internasional. Hal ini menunjukan bahwa ISIS lah yang mempengaruhi kapabilitas antar aktor dalam sistem internasional tersebut. Distribusi kekuatan Amerika Serikat yang memutuskan untuk mencampuri permasalahan di Timur Tengah [mulai dari keterlibatan Amerika dalam Perang Teluk, invansi ke Irak, Arab Spring, dan lain-lain] memicu lahirnya gerakan protes yang mengarah pada perang asimetris melawan terorisme. Keterlibatan negara lain dalam konflik Timur Tengah juga turut memberikan kontribusi terhadap situasi Timur Tengah saat ini. Distribusi kekuatan aktor di Irak dan Suriah yang pada akhirnya mendorong kelahiran ISIS. Kata kunci: ISIS, Arab Spring, Amerika Serikat, distribusi kekuatan